Prediction and interpretation of electronic spectra of transition metal complexes via the combination of molecular mechanics and angular overlap model calculations - Bernhardt, Paul V.; Comba, Peter (Inorganic chemistry, 1993)
The combination of molecular mechanics (MM) and angular overlap model (AOM) calculations has been applied in the prediction of the d-d electronic spectra of a variety of hexaamine complexes of Co(III), Cr(III), and Ni(II). Assuming that the e„ parameters (equatable with Dq) are directly proportional to r1 23456, where r is the M-N bond length, a proportionality constant, C, was determined for each type of M-N bond, i.e. M-NH3, M-NH2R, M-NHR2,and M-NR3. The C parameters were found to increase with the addition of each alkyl group for all three systems.
Gesehen am 05.09.2022